Analysis Patient Satisfaction at Poly Clinic Pulmonary Hospital Level III dr. Reksodiwiryo Padang City - Huvaid, Sevilla Ukhtil; Hilda Hidayat; Aprini Ria (Sean Institute, 2022)
Work satisfaction is a joyful emotional attitude and loves the work. This attitude is transformed by work moral, discipline, and work achievement. Relating to officers’work satisfaction, it is found there is still low discipline of the officers it is indicated from absence. The objective of this research is to know the correlating factors with officers’ work satisfaction at Sungai Penuh Public Health Center of Sungai Penuh Town. This research is analytical survey with cross-sectional design. Population of this research were all permanent officers at Sungai Penuh Public Health Center of Sungai Penuh Town amounted 49 officers. Sampling of this research is total sampling that all population become sample. Data of the research were primary and secondary data that were analyzed univariately and bivariately with chi-square test. Research findings showed that more than a half 53.1% stated that less satisfied, 46.9% stated that they were satisfied, 57.1% officers stated that leader’s attitude in leading was good, 51.0% officers stated that working condition was less comfortable, 49.0% officers stated that working condition was comfortable. There was significant correlation between working condition and officers’ satisfaction and there was no significant correlation between leaders’ attitude in leading and officers’ work satisfaction at Sungai Penuh Public Health Center of Sungai Penuh Town. It is expected to fix all aspects that cause the officers feel less satisfied in their work. It is needed cooperation both among the officers and the leaders.